Novel high strength titanium-titanium composites produced using field-assisted sintering technology (FAST). (15th January 2019) - Calvert, E.L.; Knowles, A.J.; Pope, J.J.; Dye, D.; Jackson, M.
Abstract: To increase the strength of titanium alloys beyond that achievable with α - β microstructures, alternative reinforcing methods are necessary. Here, field-assisted sintering technology (FAST) has been used to produce a novel Ti-5Al-5Mo-5V-3Cr (Ti-5553) metal-matrix-composite (MMC) reinforced with 0-25 wt.% of a ∼2 GPa yield strength TiFeMo alloy strengthened by ordered body-centred cubic intermetallic and ω phases. The interdiffusion region between Ti-5553 and TiFeMo particles was studied by modelling, electron microscopy, and nanoindentation to examine the effect of graded composition on mechanical properties and formation of α, intermetallic, and ω phases, which resulted in a > 200 MPa strengthening benefit over unreinforced Ti-5553. Graphical Abstract: